IRAN DAN KONFLIK PALESTINA: ANTARA DUKUNGAN RETORIS DAN KETERBATASAN TINDAKAN MILITER - Munawwarah, Siti Ruyatul; Rahmatulummah, Alia (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2025)
The Palestinian conflict is a central issue in Iran’s foreign policy, with Tehran consistently voicing support for the Palestinian struggle, primarily through anti-Israel rhetoric. From a realist perspective, Iran's policy on this conflict is driven by its national interest in expanding influence in the Middle East and challenging the dominance of Israel and its allies. However, despite providing financial, logistical, and military support to groups such as Hamas and Islamic Jihad, Iran’s direct military involvement remains limited. Factors within the concept of regional security, such as the balance of power, international pressure, and the risk of conflict escalation with Israel and its Western allies, restrict Iran's direct military actions. This study finds that Iran's policy toward Palestine is more symbolic and strategic in the context of domestic politics and regional alliances rather than direct military engagement. Thus, Iran relies more on an asymmetric approach by supporting non-state actors rather than engaging in open confrontation.